Caracterização morfológica e avaliação do desenvolvimento inicial de clones de Teca (Tectona grandis L.f.) - Miranda, Mariele Cunha de (2013)
The aim of this study was to verify the existence of morphological characters that distinguish clones and plants seminal Teak and evaluate the development of these clones in the field, a settlement in southwestern Mato Grosso. The work was conducted in a plantation of teak clones composed of five named 61, 62, 63, 68 and 80 and seminal plants, in the municipality of Indiavaí, southwest of Mato Grosso. Was established four plots with 25 plants for each clone and the seminal. Morphological characterization was performed by describing the characteristics of the sheets: length and width of the leaf, shape, height, base, margin, pilosity, color, venation and presence or absence of petiole. It measured the number of internodes per linear meter and qualified individuals in appearance and skin color and symptomology of diseases. For the evaluation of development measured the diameter at breast height and total height of all trees in the plot, continuing with the calculation of averages of these variables and the transverse and basal areas. The trees were also evaluated qualitatively about the state of the canopy, plant health, stem form and disease symptoms. The characteristics differing with regard to morphology were leaf base, presence or absence of petiole, pilosity, leaf length, number of internodes and presence of symptomatic plants. Regarding the development, in general, the clones expressed superiority to seminal plants. The expression of morphological characteristics and development varied according to geographic region of origin of the clones.